Helping students make progress in their careers: An attribute analysis of effective vs ineffective student development plans. Issue 3 (November 2017) - Hunt, James M.; Langowitz, Nan; Rollag, Keith; Hebert-Maccaro, Karen
Abstract: Development planning has been promoted as a useful pedagogical tool for leadership and career development beyond the classroom. In this paper, we identify the attributes of student development plans that are associated with proactive effort and significant progress after the assignment and the course are over. This study examines outcomes for 84 MBA students asked to write about their experience 18 months after completing a mandatory course-based development plan. Using content analysis we were able to compare the students' self-described career development progress against their original plans, and discern patterns among those students who subsequently made a high degree of self-reported progress versus those who showed little progress. We found that high levels of self-reported progress were associated with development plans that exhibited clear goals, thoughtful self-assessment of strengths and weaknesses, specific, realistic action steps, and an insightful understanding of the political and organizational challenges of implementing the plan. Effectiveness in career management over time appears associated with students' sense of personal agency regarding their career. The implications of this research for MBA faculty and career services are discussed. Highlights: Development planning as an assignment is widely used in management education. This retrospective study examines the impact of development planning on MBA students. The value of development planning appears to be enhanced by a sense of personal agency.